2015
DOI: 10.3389/fimmu.2014.00691
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Syntaxin 3 in the Secretion of IL-6 from Dendritic Cells Following Activation of Toll-Like Receptors

Abstract: The role of dendritic cells (DCs) in directing the immune response is due in part to their capacity to produce a range of cytokines. Importantly, DCs are a source of cytokines, which can promote T cell survival and T helper cell differentiation. While it has become evident that soluble-N-ethylmaleimide-sensitive-factor accessory-protein receptors (SNAREs) are involved in membrane fusion and ultimately cytokine release, little is known about which members of this family facilitate the secretion of specific cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…C). This rate increased on average about twofold to ~ 0.0027 bursts·s −1 ·μm −2 upon overnight stimulation with LPS, likely due to the increased expression of trafficking proteins and the rerouting of intracellular trafficking . These are coarse estimates, with a 10‐fold variation among cells (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…C). This rate increased on average about twofold to ~ 0.0027 bursts·s −1 ·μm −2 upon overnight stimulation with LPS, likely due to the increased expression of trafficking proteins and the rerouting of intracellular trafficking . These are coarse estimates, with a 10‐fold variation among cells (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The Qa-SNARE Stx3 is essential (170), and its abolishment leads to defects in secretion (61,94) and endosomal trafficking (52). Stx3 is present at the plasma membrane (94,104,109,122,312) and at various intracellular compartments (88,108,109,313,341).…”
Section: Stx3mentioning
confidence: 99%
“…As a consequence, activated dendritic cells increase the delivery rate of IL-6-containing vesicles at the plasma membrane about two-fold, as shown by quantitative imaging (Verboogen et al, 2018b). At the posttranslational level, the SNARE protein syntaxin-3, which is involved in IL-6 release, moves from intracellular compartments to the plasma membrane in LPS-activated macrophages (Collins et al, 2014). Moreover, Förster resonance energy transfer (FRET) coupled to fluorescence lifetime imaging microscopy (FLIM) revealed that LPS activation of dendritic cells results in increased formation of the complex between the SNARE protein VAMP3which is also involved in IL-6 releaseand syntaxin-4 at the plasma membrane (Verboogen et al, 2017).…”
Section: Trafficking Is Rate-limiting For Constitutive Secretion Of Cmentioning
confidence: 96%
“…Moreover, Förster resonance energy transfer (FRET) coupled to fluorescence lifetime imaging microscopy (FLIM) revealed that LPS activation of dendritic cells results in increased formation of the complex between the SNARE protein VAMP3which is also involved in IL-6 releaseand syntaxin-4 at the plasma membrane (Verboogen et al, 2017). At transcriptional and translational levels, the expression of SNAREs and many other proteins involved in trafficking of cytokines is upregulated in activated macrophages and dendritic cells (Chiaruttini et al, 2016;Collins et al, 2014;Manderson et al, 2007;Mori et al, 2011;Murray et al, 2005a;Pagan et al, 2003). Although not directly proven, this is likely to result in an increased rate of exocytic trafficking that is required to secrete all the newly synthesized cytokines.…”
Section: Trafficking Is Rate-limiting For Constitutive Secretion Of Cmentioning
confidence: 99%
See 1 more Smart Citation